Morphoanatomical study, seasonal variation, and larvicidal activity of volatile oils from the leaves of Campomanesia pubescens (DC.) O. Berg (Myrtaceae) (Research, Society and Development, 2021)
The aim of this study was to perform from the morpho-anatomical study, physicochemical characterization, chemical composition, seasonal variability and larvicidal activity of the volatile oils of Campomanesia pubescens (DC.) O. Berg leaves. The botanical material was collected in Hidrolândia, Goiás. Morpho-anatomical characterization and phytochemical screening were performed by conventional methods. Leaf powders were submitted to hydrodistillation in the Clevenger apparatus and the identification of the chemical components of the volatile oils obtained was done by GC-MS. The larvicidal activity was carried out with third-stage larvae of the Aedes aegypti. The leaf blade, the main vein, and the young stem have a uni-stratified epidermis covered by a cuticle. The mesophyll and cortical parenchyma of the main vein and young stem have secretory cavities and idioblasts with crystals. The main rib contains a bicolateral bundle in an open arch. The young stem has a discontinuous band of sclerenchyma external to the phloem cells. Most volatile oil compounds are spathulenol, caryophyllene oxide, α-macrocarpene, and z-caryophylleneIn phytochemical analysis, tannins, digitalis, flavonoids, and total phenols were detected. The content of volatile compounds was 7.36%, that of total ash was 1.77%, and that of mucilage was 3.52 ml. The volatile oil at the concentration used was inactive against Ae aegypti larvae. The present study contributes to the taxonomic knowledge of the species and provides parameters for quality control of the plant raw material. This work represents the first description of the chemical compounds and seasonal variability of volatile oils from C. pubescens leaves collected in Goiás state.